2017
DOI: 10.1016/j.envexpbot.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Can a low concentration of an organophosphate insecticide cause negative effects on an aquatic macrophyte? Exposure of Potamogeton pusillus at environmentally relevant chlorpyrifos concentrations

Abstract: The contamination of the aquatic environments with organophosphorus pesticides may affect non-target organisms. The aim of this study was to evaluate the toxic effects of the insecticide chlorpyrifos (CPF) at environmental concentrations on the freshwater macrophyte Potamogeton pusillus belonging to a genus of worldwide distribution. For this purpose, individuals were exposed from 3.5 to 94.5 ng of CPF L À1 for 96 h. A battery of biochemical responses including bioaccumulation, defense and damage biomarkers we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 69 publications
2
8
0
1
Order By: Relevance
“…Despite the fact that in the last years there was an increase of the use of IBR indices both in plant and animals in laboratory experiments (Bertrand et al, 2016b(Bertrand et al, , 2017 or field studies (Santos et al, 2016), few of them are applied for defining processes or modes of toxicity. For example, for mussels IBR indices were developed for inmunotoxical (Auffret et al, 2006) and lysosomal biomarkers (Izagirre and Marigomez, 2009) to evaluate contaminated sites.…”
Section: Integrated Biomarker Responsementioning
confidence: 99%
“…Despite the fact that in the last years there was an increase of the use of IBR indices both in plant and animals in laboratory experiments (Bertrand et al, 2016b(Bertrand et al, , 2017 or field studies (Santos et al, 2016), few of them are applied for defining processes or modes of toxicity. For example, for mussels IBR indices were developed for inmunotoxical (Auffret et al, 2006) and lysosomal biomarkers (Izagirre and Marigomez, 2009) to evaluate contaminated sites.…”
Section: Integrated Biomarker Responsementioning
confidence: 99%
“…org). Previous studies reported Potamogeton capacity to evidence pollutants exposure under laboratory conditions (Bertrand et al, 2016(Bertrand et al, , 2017Costa et al, 2018;Monferr an et al, 2009). In a similar way, others authors described the usefulness of Potamogeton in passive monitoring programs, showing to be useful as a biological indicator while evaluating environmental deterioration (Demirezen and Aksoy, 2004;Harguinteguy et al, 2016;Munteanu and Munteanu, 2007).…”
Section: Introductionmentioning
confidence: 73%
“…Individuals of South American native macrophyte, P. pusillus, were collected from a reference site located in a tributary (Yuspe River) of the Suquía River upper basin based on an earlier study (Bertrand et al, 2017). Organisms were acclimated during two weeks in glass aquaria filled with 10% Hoagland's solution, sediments (1/4) from the same sampling area, and they were maintained at 25 ± 1 C under a natural light: dark regime.…”
Section: Monitoringmentioning
confidence: 99%
See 2 more Smart Citations